2021
DOI: 10.1016/j.ejca.2021.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of quality of life in patients with human epidermal growth factor receptor 2–positive metastatic breast cancer treated with tucatinib or placebo when added to trastuzumab and capecitabine (HER2CLIMB trial)

Abstract: Aims: In HER2CLIMB, tucatinib significantly improved progression-free and overall survival in patients with human epidermal growth factor receptor 2epositive (HER2þ) metastatic breast cancer. We evaluated the impact of tucatinib on health-related quality of life (HR-QoL) in HER2CLIMB. Methods: Patients were randomised 2:1 to tucatinib or placebo combined with trastuzumab and capecitabine. Starting with protocol version 7, the EuroQol 5 Dimensions 5 Levels (EQ-5D-5L) questionnaire and EQ visual analogue scale (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Using the EuroQol 5 Dimensions 5 Levels instrument, the tucatinib combination was found to preserve health-related quality of life throughout treatment. 33 Finally, the proportions of patients who received additional anticancer therapies post-progression in tucatinib combination and placebo combination groups were high and comparable, suggesting that tucatinib combined with trastuzumab and capecitabine is sufficiently well tolerated for patients to receive additional treatments.…”
Section: Discussionmentioning
confidence: 93%
“…Using the EuroQol 5 Dimensions 5 Levels instrument, the tucatinib combination was found to preserve health-related quality of life throughout treatment. 33 Finally, the proportions of patients who received additional anticancer therapies post-progression in tucatinib combination and placebo combination groups were high and comparable, suggesting that tucatinib combined with trastuzumab and capecitabine is sufficiently well tolerated for patients to receive additional treatments.…”
Section: Discussionmentioning
confidence: 93%
“…The scenario is rapidly evolving after the investigation of tucatinib in the HER2CLIMB trial on HER2+ metastatic BC, which displayed superiority in all the planned outcomes, such as PFS, OS, objective response rate [ 36 ] and quality of life [ 37 ] including in patients with BM [ 38 ]. Recently, Murthy et al reported the results of a phase 2 TBCRC049 trial focused on 17 patients with LM from HER2-positive BC, who were treated with tucatinib, trastuzumab, and capecitabine: an i-PFS of 6.9 months (95% CI 2.3–13.8) and an OS of 10 months (95% CI 4.1-not reached) were observed [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…An evaluation of the impact of tucatinib on health-related quality of life (HR-QoL) in HER2CLIMB demonstrated that HR-QoL was preserved for patients with HER2-positive mBC who were treated with tucatinib when added to trastuzumab and capecitabine. Additionally, HR-QoL was maintained longer with tucatinib therapy than with placebo among those with BM [ 11 ].…”
Section: Resultsmentioning
confidence: 99%